IN THE FIGHT AGAINST JUSTICE AND CORRUPTION AS AN EFFECTIVE ROAD (E Conference Zone, 2022)
In this article of the state basic foundations which was justice of the principle corruption prevent taking role, society in life this of understanding position and role about word goes.